Lack of seasonal variation in the incidence of eosinophilic oesophagitis in adolescent and adult non-PPI-responsive oesophageal eosinophilia midwestern US populations. Issue 2 (April 2014) - Frederickson, Nicholas W; Bayman, Levent; Valestin, Jessica; Redd, Matthew; Lee, Ye-Jin; Soubra, Mahmoud; Schey, Ron
Background: Eosinophilic oesophagitis (EoO) has been associated with allergic disorders as well as aeroallergens. The current literature has shown a possible association between seasonal variation, mainly in the spring, and the incidence of EoO. However, this data was based on small population studies that did not exclude proton-pump inhibitor (PPI)-responsive oesophageal eosinophilia (PPI-ROE) in their cohort. Aim: The aim of this study was to determine if there is a seasonal variation associated with the diagnosis of EoO in patients that had been treated with high-dose PPI prior to diagnosis. Methods: Oesophageal biopsies were obtained from a cohort of patients who presented with symptoms of dysphagia, odynophagia, and heartburn during a 10-year period. Symptomatic patients who had biopsies from the mid and distal oesophagus with ≥20 eosinophils per high-power field (hpf) while on high-dose PPI treatment for at least 5 weeks were diagnosed as having EoO. The monthly and seasonal incidences were determined (winter, January–March; spring, April–June; summer, July–September; Autumn, October–December). Results: A total of 20, 718 patients were identified and their records evaluated. From this cohort, 193 (0.93%) symptomatic patients had biopsy-proven oesophageal eosinophilia (≥20 eosinophils/hpf) and no seasonal variation was seen in this group. However, only 57 (0.28%) had been adequately treated with PPI prior to diagnosis (i.e. non-PPI-ROE biopsy-proven EoO; ≥20 eosinophils/hpf: 39 males, 18 females; age 29.5 years). The most common medical history components included asthma (12.3%) and food allergies (3.5%), and the most common presenting symptoms included dysphagia (50.9%) and heartburn (26.3%). The monthly and seasonal incidences in our cohort were with no apparent trend ( p = 0.713 and 0.703, respectively). Conclusions: The incidence of EoO was consistent across all 12 months as well as during the four seasons. Our data does not support a seasonal variation in relation to the incidence of EoO in the US midwestern non-PPI-ROE population.